“We’re Ready to Fight”: Interview with Ontario Education Workers United Member, Deborah Buchanan-Walford - Maton, Rhiannon (Critical Education, 2022)
In this interview, Ontario Education Workers United (OEWU) member Deborah Buchanan-Walford talks with Rhiannon Maton about how the OEWU engages in grassroots organizing for improved working and learning conditions in Ontario, Canada public schools. We discuss the learning and workplace challenges experienced in adult day schools during Covid-19, issues of power centralization within the broader educators union, and the significance of activist educators organizing in spaces that are external to their union.